Comportamento lúdico de crianças pré-termo e seu desenvolvimento neuropsicomotor - Rombe, Patrícia Gonçalves (2012)
The birth of a child preterm and with low birth weight is considered one of the main risk factors that can lead to changes and delays in neuro-psychomotor development. Among these changes are the difficulties in motor, learning, and visual-motor integration areas, as well as sensory and perceptive problems that alone or in combination, ultimately will impact the child's social participation, especially in carrying out activities of daily living, school and play. Considering playing as the main activity for children, this study aimed to investigate possible correlations between the performance of the ludic behavior of children with a history of preterm birth and their neuro-psychomotor development. We tried to understand this phenomenon in the pre-school period, in order to produce knowledge in a preventive perspective in relation to schooling. This study was approved by the Ethics Committee of Universidad Federal de São Carlos. It is a descriptive and correlational study involving 52 children divided into three groups: Study group GI (consisting of 12 children with a history of prematurity and low birth weight at risk of developmental delay detected), Study group GII (consisting for 14 children with a history of prematurity and low birth weight without developmental delay detected) and the comparison group GIII (without the mentioned history and with 26 children from the same socioeconomic class according to the classification made by the Criteria Questionnaire Brazil). Three methods were used to perform the evaluations: TSDD-II (Screening Test Denver II), the EPP-DP (teacher s perception scale on student s performance and participation in the school environment), and ELPK-rb (Knox s Pre-school Ludic Scale - Revised). The first test was used to compose samples, the second to raise the awareness of teachers of the development of children, and the latter to the specific assessment of ludic behavior. The data were analyzed quantitatively in order to verify the presence of significant differences in ludic behavior in the three groups. To verify the significance of possible associations between groups of preterm and term infants, with the results obtained from the TSDD-II, we chose Fisher s Exact Test. After verifying the association between the variables of interest, we used the Kruskal-Wallis Test in order to ascertain whether or not differences exist between the scores obtained by the classes of variables in the ELPK-rb participation fields. The results of this study revealed that from a detailed analysis of the play behavior of children, that is, the way the play you can identify the presence of changes in global development, as well as in more specific areas of human development. Regarding the performance of children with a history of prematurity ande risk for developmental delay 8% had unsatisfactory results and 17% were assessed as having a partially satisfactory performance, something that was not repeted in the other groups analyzed, which had in most cases very satisfactory performances. A similar picture was observed when analyzing the performance of children in fine motor activities, where children with a history of prematurity had inferior performances to those of children born at term, principally when comparing the results obtained from children of group GI with those obtained from children in group GIII. Regarding the results obtained in evaluating the ELPK-rb participation field, lmost all children from groups GI, GII and GIII presented co-operative play behavior, or would rather play only with other children. Another factor that draws our attention when observing the results of participation fields, was the presence of a greater difficulty for children with a history of prematurity and risk for developmental delay in playing games with simple rules (being that 17% did not show the expected behavior and 25% played tentatively). Still with respect to the participation field, when analyzing the results related to the language area it was observed, again, a lower performance among children with a history of prematurity, especially among children in group GI, when compared to children born at term. Regarding the children s performance in the ELPK-rb field of make believe/symbolic games, it was noted that children of the group GI obtained results lower tah those of children from GII and GIII, especially in sub-items interprets more complex emotions and demonstrates function in the games for or with others . By establishing the association between the results obtained by the groups in ELPK-rb, with those presented in TSDD-II, it was observed that there are changes in play behavior of children with a history of prematurity, due to possible delays in neuro-psychomotor development, once working with all comparisons involved, the results presented by children in strata 1 (with a history of prematurity and risk for developmental delay) differed from the children in strata 4 (born at term and with the presence of caution ). However, we cannot say that the presence of risk for developmental delay detected by TSDD-II, as well as changes in play behavior of children are unique conseqyuences of prematurity, but that they results from multiple factors that add up and influence, concomitantly, the development of motor, cognitive, psychological, and social skills of children. It is confirmed then, that pratical education, health, and social skills of children. It is confirmed then, that pratical education, health, and the promoting of development occur in conjunction, contributing to the detection of risk factors and promoting the quality of interactions and the environment in which children are placed. In this sense, it is necessary to invest in the training of educators/caregivers/pages, since they can provide protective factors in children s development, minimizing/offsetting the negative effects arising from the presence of social and biological risk factors through play, as this constitutes one of the main activities performed by children in preschool, and whose primary essence is the promotion of cognitive and bio-psychomotor development in the subjects. To give children opportunities to play is to give them much more than the act itself, because it provides to each of them a better perspective of life and natural and healthy development.